Implementation of Gyrinops Versteegii Gaharu Leaves as a Dye-Sensitized Solar Cell - Mashari, Reza Maulana; Prihanto, Dwi (Universitas Negeri Malang, 2019)
Dye-Sensitized Solar Cell (DSSC) is a photoelectrochemical solarcell that uses electrolytes as the cargo transport medium. Gratzeldeveloped it as an alternative resource through the discovery of thelatest solar cell material by mimicking the photosynthesis processcalled photo-electrochemical reactions. According to the researchof Saputra, flavonoids can be used as dyes in Dye-Sensitized SolarCells, while Yanti in 2014 studied the agarwood leaf extract thatcontained flavonoids and chlorophyll. This study aimed to design,build, and test Dye-Sensitized Solar Cell by testing the lightabsorption, and the Performance of Dye-Sensitized Solar Cell usingAgarwood Chlorophyll. This research extracted the Gyrinopsversteegii that was grouped into young, medium and old leaves.With the same dose of extract, 15 grams of agarwood leaves weredissolved in 96% ethanol for 100 ml. The results showed that eventhough the maximum absorption power was the same, or 4.00, themedium leaves absorbed the light more than its wavelength range.The DSSC performance test results obtained the voltages of theyoung, medium, and old agarwood leaves that were 0.398 V, 0.399V, and 0.369 V. The currents of those leaves were 0.01 mA, 0.01mA, and 0.01 mA respectively.